Estudio de caso: Propuesta pedagógica orientada a mejorar el desarrollo integral de un niño de 3 a 4 años del centro de desarrollo integral andares ubicado en la ciudad de Loja, periodo 2021-2022. - Guaman Jaramillo, Jessica Fernanda (2022)
The present investigation entitled: Study case: pedagogical proposal guided to improve the integral development of a child from 3 to 4 years old from the integral development center "andares"of the loja city, period 2021-2022.The general objective was to identify through the study case how it favors the application of a specific pedagogical proposal to improve the integral development of a child from 3 to 4 years old. The research design was qualitative, it worked with a child in a personalized way, its scope was descriptive, the methods used were analytical-synthetic, inductive-deductive, and the abbreviated development scale of Nelson Ortiz was used as an instrument,with the application it was determined that the child was at a medium level in the gross and fine motor areas and alert in hearing, language and social personnel, that being in the state of alert should be treated with priority taking into consideration that they are very important aspects in neuroevolutionary development. To solve the problem was developed and executed a guide of activities called "playing I learn", as a didactic strategy for the improvement of integral development, after this the post test was applied, thus evaluating the impact of the intervention obtaining positive results, locating at a medium-high level in all areas, concluding that the application of the personalized pedagogical proposal helped to improve the integral development of the child. Keywords. Comprehensive Development, Pedagogical Proposal, Areas of Development, Game, Stimulation.